Konstruksi Pemberitaan Media Online Tentang Kasus Penembakan Enam Anggota Laskar Front Pembela Islam: Analisis Framing Robert N. Entman pada Republika.co.id dan Kompas.com Periode Desember 2020 - Januari 2021 - Abdul Malik; Dedi Priyadi (Jurnal Inovasi dan Kreativitas (JIKa), 2022)
Abstract Problems: In early December 2020, the public was shocked by the shooting of six members of the Islamic Defenders Front Organization (FPI) at the Jakarta-Cikampek Toll Road. The case attracted media attention, so it became the main topic in the news. Two of the media that intensely reported on the case were Kompas.com and Republika.co.id. In their reporting, the two media have different points of view so that it is interesting to investigate further. Purpose: to find out how the online media Kompas.com and Republika.co.id carried out the construction on their reports about the shootings of six FPI soldiers. Methodology: This study uses the framing analysis method of the Robert N. Entman model. Framing analysis is used to find out how reality is constructed by the media. In what ways and techniques are events emphasized and highlighted. Is there a part in the news that is omitted, missed, or even hidden in the news? Results/Findings: The research findings show that the construction constructed by Kompas.com is inconsistent between the early and mid-period, in which Kompas.com was initially a police informant, but later switched to viewing this case as a humanitarian tragedy. Meanwhile, Republika.co.id tends to be more consistent in the construction it builds, where from the start, Republika has favored the FPI and denounced unlawful killings as a humanitarian tragedy. Paper Type: field research Keywords: FPI, unlawful killing, social construction, framing analysis